2014
DOI: 10.1371/journal.pone.0107070
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Design Evaluation Tool for Handheld Device Soft Keyboards

Abstract: Thumb interaction is a primary technique used to operate small handheld devices such as smartphones. Despite the different techniques involved in operating a handheld device compared to a personal computer, the keyboard layouts for both devices are similar. A handheld device keyboard that considers the physical capabilities of the thumb may improve user experience. We developed and applied a design evaluation tool for different geometries of the QWERTY keyboard using a performance evaluation model. The model u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In order to retain the consistent reliability of study results for elderly participants, the present study adopted the identical method retrieved from the previous study. In addition, the task settings of both two studies referred to those in previous studies reported by Trudeau et al ( 2012a , b , 2014 ), and hence some similarities in the experimental task settings among these studies can be found in the present study.…”
Section: Methodssupporting
confidence: 72%
“…In order to retain the consistent reliability of study results for elderly participants, the present study adopted the identical method retrieved from the previous study. In addition, the task settings of both two studies referred to those in previous studies reported by Trudeau et al ( 2012a , b , 2014 ), and hence some similarities in the experimental task settings among these studies can be found in the present study.…”
Section: Methodssupporting
confidence: 72%
“…Second, tapping constitutes a subtask of typing, and thus performance for taps at specific locations on the screen can be used to predict the performance for more complex tasks. A predictive evaluation model can thus be developed for small mobile device keyboard designs to determine which design may lead to better performance, as shown by Trudeau et al (2014). Third, simple tapping tasks are important as they are commonly used in gaming, selecting applications or dialing on a number pad.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should evaluate the usability and user experience with curved keyboards in more robust mobility scenarios (i.e., standing, walking). Additionally, keyboard configurations aligned with the middle of the screen should also be explored per the findings of Trudeau (2014).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the curved QWERTY yielded the least input efficiency when evaluating the accuracy and reaction time during typing of randomly paired characters. Although several of the aforementioned studies show evidence against curved layouts (Chang et al, 2017;Trudeau et al, 2014), screen size has yet to be thoroughly investigated in relation to objective and subjective performance metrics with a curved keyboard. While previous studies have identified various issues related to current mobile keyboard design, none have evaluated the effect of one versus two-handed use as it relates to varying screen sizes and keyboard layouts using representative user typing tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation